Comparison of Extracorporeal Shock Wave Therapy versus Manual Lymphatic Drainage on Cellulite after Liposuction: A Randomized Clinical Trial. (10th August 2021) - Allam, Nesma M.; Elshorbagy, Radwa T.; Eid, Marwa M.; Abdelbasset, Walid Kamal; Elkholi, Safaa Mostafa; Eladl, Hadaya Mosaad
Abstract : Introduction . Cellulite is associated with variations in the skin appearance with cottage cheese, mattress-like, or orange peel. The most common areas for these lesions are the posterior or upper thighs and buttocks and mainly affect females after puberty. The objective of the study was to determine whether extracorporeal shock wave therapy (ESWT) or manual lymphatic drainage (MLD) is more effective for the reduction of the grade of cellulite after liposuction. Methods . This study is a single-blinded randomized controlled clinical trial. Thirty females with grade 3 cellulite were randomly distributed into two groups equal in number ( n = 15), group A was equipped to ESWT and group B was equipped to MLD. The cellulite grading scale was used to assess cellulite grade, and the skinfold caliper was used to assess the thickness of subcutaneous fat. The assessment was carried out before and four weeks after starting the treatment. Both groups received topical retinol twice daily for four weeks; in addition, group A received ESWT, while group B received MLD, two times/week for 4 weeks. Results . The mean values of the skinfold caliper in group A decreased by 24.4% and in group B by 15.38% with a significant difference between the two groups p < 0.001 . Also, the mean values of the cellulite grading scale decreased significantly after treatment in group A compared with the mean values of group B p < 0.001 . Conclusions . There was more reduction in the grade of cellulite and thickness of subcutaneous fat in the ESWT group than the MLD group after liposuction.